Mitochondrial Dysfunction, Neurogenesis, and Epigenetics: Putative Implications for Amyotrophic Lateral Sclerosis Neurodegeneration and Treatment - Calió, Michele Longoni; Henriques, Elisandra; Siena, Amanda; Bertoncini, Clélia Rejane Antonio; Gil-Mohapel, Joana; Rosenstock, Tatiana Rosado (Frontiers in Neuroscience, 2020)
Amyotrophic Lateral Sclerosis (ALS) is a progressive and devastating multifactorial neurodegenerative disorder. Although the pathogenesis of ALS is still not completely understood, numerous studies suggest that mitochondrial deregulation may be implicated in its onset and progression. Interestingly, mitochondrial deregulation has also been associated to changes in neural stem cells (NSCs) proliferation, differentiation and migration. In this review, we highlight the importance of mitochondrial function for neurogenesis, and how both processes are correlated and may contribute to the pathogenesis of ALS; we have primarily focused on preclinical data from animal models of ALS, since to date no studies have evaluated this link using human samples. Since there is currently no cure and no effective therapies to counteract ALS, we have also discussed how improving neurogenic function by epigenetic modulation could benefit ALS. In support of this hypothesis, changes in histone deacetylation can alter mitochondrial function, which in turn might ameliorate cellular proliferation as well as neuronal differentiation and migration. We propose that modulation of epigenetics, mitochondrial function and neurogenesis might provide new hope for ALS patients, and studies exploring these new territories are warranted in the near future.